The therapeutic use of music as experienced by cardiac surgery patients of an intensive care unit - Varshika M. Bhana; Annali D.H. Botha (AOSIS, 2014)
Patients perceive the intensive care unit (ICU) as being a stressful and anxiety-provoking environment. The physiological effects of stress and anxiety are found to be harmful and therefore should be avoided in cardiac surgery patients. The aim of the study on which this article is based was to describe cardiac surgery patients' experiences of music as a therapeutic intervention in the ICU of a public hospital. The objectives of this article were to introduce and then expose the cardiac patients to music as part of their routine postoperative care and to explore and describe their experiences of the music intervention. The findings of the research are to be the basis for making recommendations for the inclusion of music as part of the routine postoperative care received by cardiac surgery patients in the ICU. A qualitative research methodology, using a contextual, explorative and descriptive research design, was adopted. The population of the study was cardiac surgery patients admitted to the ICU of a public hospital. An unstructured interview was conducted with each participant and content analysis and coding procedures were used to analyse the data. Four main themes were identified in the results, namely practical and operational aspects of the music sessions; participants' experiences; discomfort due to therapeutic apparatus and the ICU environment; and the role of music and recommendations for music as a therapeutic intervention. Participants' experiences were mainly positive. Results focused on experiences of the music and also on the participants' experiences of the operational aspects of the therapy, as well as factors within and around the participants. Pasiënte se persepsie van die intensiewesorgeenheid (ISE) is dat dit 'nstresvolle en angswekkende omgewing is. Die fisiologiese effekte van stres en angs is skadelik en daarom moet dit vermy word in die geval van pasiënte wat hartchirurgie ondergaan. Die doel van die studie waarop hierdie artikel gebaseer is, was om hartchirurgiepasiënte se ervaring van musiek as 'n terapeutiese intervensie in die ISE van 'nopenbare hospitaal te beskryf. Die doelwitte van hierdie studie was om hartchirurgiepasiënte bekend te stel aan musiek as deel van hul roetine- postoperatiewe sorg en hulle dan daaraan bloot te stel om sodoende hulle ervarings van die musiekintervensie te ondersoek en beskryf. Die bevindinge van die navorsing sal gebruik word om aanbevelings te maak vir die insluiting van musiek as deel van die roetine- postoperatiewe sorg wat hartchirurgiepasiënte in die ISE ontvang. 'nKwalitatiewe navorsingsmetodologie, met behulp van 'nkontekstuele, verkennende en beskrywende ontwerp, is gebruik. Die populasie van die studie was hartchirurgiepasiënte in die ISE van 'nopenbare hospitaal. 'nOngestruktureerde onderhoud is met elke deelnemer gevoer en inhoud-analise en koderingprosedures is gebruik om die data te ontleed. Vier hooftemas is in die resultate geïdentifiseer, naamlik praktiese en operasionele aspekte van die musieksessies; die deelnemers se ervarings; ongemak as gevolg van terapeutiese apparaat en die ISE-omgewing; asook die rol van musiek en aanbevelings vir musiek as 'nterapeutiese intervensie. Deelnemers se ervarings was hoofsaaklik positief. Die resultate het gefokus op die deelnemers se ervaring van die musiek asook hul ervaring van die operasionele aspekte van die terapie, sowel as faktore binne en rondom die deelnemers.